The «Blue Dot Network» project as a response to the «The Belt and Road» Initiative - Mussataev, S.; Ashimbay, N.; Orazakynkyzy, F. (Journal of Oriental Studies, 2021)
One of the most important projects of modern economic cooperation is the “Belt and Road”, initiated by China. Modernization of the Great Silk Road is an important project of the XXI century and its development will have a positive impact on the entire Eurasian space. This mega-project is equal to a trade, economic, cultural and spiritual bridge between Europe and Asia. However, in 2019, the US, Japan and Australia jointly proposed the Blue Dot Network project in response to the Belt and Road Initiative. thus, the struggle for a zone of influence in world politics and the global economy takes on a new character. therefore, the analysis of the causes and consequences of the “blue dot network” project in response to the “belt and road” initiative, its impact on political and economic processes at the global and regional levels is relevant. In modern world politics, major powers are fighting in a new way to expand their influence and protect their interests, and in this struggle, trade and economic sanctions are coming to the fore. The emergence of competition between the Blue Dot Network project and the Belt and Road initiative, in turn, can exacerbate the global economic crisis, combining with factors such as COVID-19, the trade war. The Belt and Road Initiative is of paramount importance not only for China, but also for all countries along the Silk Road, so the scientific and practical significance of studying this issue is not in doubt. The goal of the three countries united in the “Blue Dot Network” project (USA, Japan, Australia) is to regain control and influence over the Asia – Pacific region, and the Belt and Road initiative proposed by China is to develop Eurasian trade integration, promote mutually beneficial ties and infrastructure development between the countries of the region. Comparing the features of these two projects will help to identify the circumstances that negatively affect global and regional cooperation, prevent possible risks, and develop integration processes. the conducted research contributes to the understanding of new political and economic realities emerging in the field of international relations, the development of integration processes in the global and regional space, contributes to the deepening of multilateral mutually beneficial cooperation of the project within the framework of the “belt and road”initiative. Key words: integration, cooperation, «Blue Dot Network» project, «Belt and road» initiative, trade and economic wars.